DEVELOPMENT OF MULTIMEDIA LEARNING SCIENCE FOR PRIMARY SCHOOLS BASED ON CONSTRUCTIVISTIC LEARNING THEORY - Nur Ngazizah; Titi Anjarini (Universitas Sebelas Maret, 2018)
This study aims to develop learning multimedia that can be used in learning for fifth grade elementary school students. Multimedia development is aimed at blood competence.This research is a development research with a 4-D model (four D model) proposed by Thiagarajan, which consists of four stages. The four stages are define, design, development and dissemination stages. disseminate). In the define stage, a curriculum review is conducted related to the competence of flat building. The results from the define phase are used as a reference for multimedia design. The next stage is design, at this stage has produced draft-1 results of the review and design in the previous stage. The next stage is development, at this stage draft I is validated by material experts and media experts . In general, material experts gave an assessment that multimedia draft I was in accordance with KTSP and constructivistic learning theory. Media experts judge that multimedia is easy to use. The first draft was valid with revisions clarifying blood circulation construction, simplifying the start menu, adding quiz 1, and adding motion animations at the beginning and end of the slide to make it more interesting. After the revised draft I developed into draft II to be tested in the classroom. Small scale 17 students in grade V SD N Purworejo Purworejo Regency. This trial is to find out the response of students. In this stage, an observation was also made by 1 teacher regarding the use of multimedia to complete the teacher's response questionnaire. The results of the teacher and student response questionnaire showed that 17 students were satisfied with multimedia draft II and students increasingly understood the blood flow system, circulatory structure, blood type and diseases of the blood. The revision towards draft III is the addition of applause as a tribute to students. As far as the stages of research have been carried out, it can be said that multimedia development can be used in the learning process and get positive responses from students. The next research phase is to conduct large-scale trials with more (two-class) research samples. The results of the trial will produce the final product which will then be disseminated (dessiminate stage).